Progressive Bone Formation After Cervical Disc Replacement: Minimum of 5-Year Follow-up. Issue 3 (1st February 2018) - Zhou, Feifei; Ju, Kevin L.; Zhao, Yanbin; Zhang, Fengshan; Pan, Shengfa; Heller, John G.; Sun, Yu
Abstract : Study Design: Retrospective review. Objective: Our objective was to examine the prevalence, clinical significance, ramifications, and possible etiology of postoperative bone formation at the index level after cervical disc replacement (CDR) with a minimum of 5 years of follow-up. Summary of Background Data: CDR can be complicated by postoperative ossification and unwanted ankylosis at the index level, which some authors have termed "heterotopic ossification." This terminology may be inaccurate as it assumes the postoperative bone formation is unnatural and a consequence of the CDR surgery. We advocate that this phenomenon has more to do with individual patient factors rather than the surgery. Methods: Patients who underwent Bryan CDR for cervical myelopathy or radiculopathy between 12/2003 and 8/2008 with a minimum of 5-years follow-up were analyzed. They were divided into two groups, those with and without postoperative bone formation. Patient-reported outcomes (Japanese Orthopaedic Association score, Neck Disability Index, Visual Analogue Scale for neck and arm pain) and radiographic parameters were collected pre- and postoperatively and compared between groups. Results: Sixty-one patients (76 levels) were identified (mean follow-up 94.2 mo). The overall incidence of postoperative ossification was 50%. Both groups had sustained significant improvements across all patient-reported outcome measures at final follow-up. Notably, patients with more severe preoperative cervical spondylosis had higher rates of postoperative ossification ( P  = 0.036) and adjacent segment degeneration ( P  = 0.010). Conclusion: Although the long-term incidence of postoperative bone formation after CDR was relatively high, this did not adversely affect patient outcomes. Patients with more severe preoperative spondylosis had higher rates of postoperative ossification, suggesting that postoperative ossification at the CDR segment is likely one of progressive bone formation in individuals already predisposed to forming bone rather than one of alleged heterotopic ossification as a consequence of the surgery. Level of Evidence: 3